Assessment of thermal changes in water buffalo mobilized from the paddock and transported by short journeys - Rodríguez-González, Daniela; Guerrero Legarreta, Isabel; Cruz-Monterrosa, Rosy G.; Napolitano, Fabio; Titto, Cristiane Gonçalves; Abd El-Aziz, Ayman H.; Hernández-Avalos, Ismael; Casas-Alvarado, Alejandro; Domínguez-Oliva, Adriana; Mota-Rojas, Daniel (Frontiers in Veterinary Science, 2023)
Evaluating the welfare of buffaloes during transport is key to obtaining and commercializing high-quality meat products; however, effective assessments require recognizing several stressors that activate physiological mechanisms that can have repercussions on the health and productive performance of species. This study used infrared thermography (IRT) to evaluate the surface temperature of 624 water buffaloes (Buffalypso breed) during 12 short trips (average duration= 2 h ± 20 min) by focusing on 11 regions of the body and face (lacrimal caruncle, periocular area, nasal region (nostril thermal window), auditory canal, lower eyelid, parieto-frontal zone, and the thoracic, abdominal, appendicular, dorsal, and lumbar regions). Recordings were made during seven phases: paddock (P1), herding (P2), corral (P3), chute handling (P4), shipping (P5), pre- (P6), and post-transport (P7). A total of 48,048 readings were obtained from 11 thermal windows. The results showed that the surface temperatures of the windows increased by as much as 5ºC during P2, P3, P5, P6, and P7 compared to P1 and P4 (p<0.0001). Differences of at least 1 ºC were also observed between windows in the craniofacial, lateral corporal, and peripheral zones (p<0.0001). Finally, a strong positive correlation (r=0.9, p<0.0001) was found between the windows. These findings lead to the conclusion that the surface temperature of the craniofacial and corporal regions of buffaloes transported for short periods varied in relation to the phase of mobilization (from paddock to post-transport), likely as a response to stressful factors, since herding and loading increased the thermal values in each window. The second conclusion is that there are strong positive correlations between central and peripheral thermal windows.